Cost-effectiveness analysis of extended endoscopic lumbar foraminotomy (EELF) and transforaminal lumbar interbody fusion (TLIF): a prospective observational study - Jun-Hoe Kim; Hangeul Park; Chang-Hyun Lee; Chi Heon Kim (Scientific Reports)
Abstract Lumbar foraminal stenosis can be surgically treated by foraminal decompression or facet joint resection and fusion (transforaminal lumbar interbody fusion, TLIF). While conventional foraminal decompression poses a risk of segmental instability, the endoscopic approach (extended endoscopic lumbar foraminotomy, EELF) resects only the ventral part of the facet joint with a horizontal surgical trajectory. A prospective observational study was performed to analyze the cost-effectiveness of EELF versus TLIF. Patients with dominant unilateral radicular pain from lumbar foraminal stenosis at or above L4-5, without severe central stenosis or instability, were included from January 2021 to February 2023. EELF involved sufficient foraminal widening using a reamer, followed by an endoscopic procedure. The primary outcome was the cost per quality-adjusted life year (QALY) gain at postoperative 12 months. Among 26 patients in each group, the primary analysis included 23 EELF patients (mean age: 72 ± 8 years) and 22 TLIF patients (mean age: 70 ± 8 years). EELF was significantly more cost-effective (EELF: $15,536.0 ± 4,190.0/QALY vs. TLIF: $32,869.4 ± 5,429.3/QALY, p < .001) and demonstrated shorter operating times, less blood loss, and shorter length of stay (p < .05), with no significant difference in clinical outcomes. Thus, EELF could be a cost-effective and less invasive alternative for treating lumbar foraminal stenosis.